Yindanxinnaotong, a Chinese compound medicine, synergistically attenuatesatherosclerosis progress - Long Cheng; Guo-feng Pan; Xiao-dong Zhang; Jian-lu Wang; Wan-dan Wang; Jian-yong Zhang; Hui Wang; Ri-xin Liang; Xiao-bo Sun (Scientific Reports)
Abstract Yindanxinnaotong (YD), a traditional Chinese medicine, has been introduced toclinical medicine for more than a decade, while its pharmacological properties arestill not to be well addressed. This report aimed to explore theanti-atherosclerosis properties and underlying mechanisms of YD. We initiallyperformed a computational prediction based on a network pharmacology simulation,which clued YD exerted synergistically anti-atherosclerosis properties by vascularendothelium protection, lipid-lowering, anti-inflammation and anti-oxidation. Theseoutcomes were then validated in atherosclerosis rats. The experiments providedevidences indicating YD’s contribution in this study included, (1)significantly reduced the severity of atherosclerosis, inhibited reconstruction ofthe artery wall and regulated the lipid profile; (2) enhanced antioxidant power,strengthened the activity of antioxidant enzymes and decreased malondialdhydelevels; (3) significantly increased the viability of umbilical vein endothelialcells exposed to oxidative stress due to pretreatment with YD; (4) significantlyreduced the level of pro-inflammatory cytokines; (5) significantly down-regulatedNF-kB/p65 and up-regulated IkB in the YD-treated groups. Overall, these resultsdemonstrated that YD intervention relieves atherosclerosis through regulatinglipids, reducing lipid particle deposition in the endothelial layer of artery,enhancing antioxidant power and repressing inflammation activity by inhibiting thenuclear factor-kappa B signal pathway.